2020
DOI: 10.1109/jphot.2020.2966533
|View full text |Cite
|
Sign up to set email alerts
|

Quadratic Soliton Combs in Doubly Resonant Dispersive Optical Parametric Oscillators

Abstract: We present temporal quadratic solitons in doubly resonant temporal dispersive optical parametric oscillators without a walk-off in numerical simulations. In frequency domain, these cavity solitons correspond to coherent dual-combs with smooth envelopes in half-harmonic and pump fields. We also investigate the soliton existence region, and the soliton behavior with parameters in this cavity system. We believe our work offers valuable insights into the practical generation of quadratic soliton combs in optical p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…This fact aroused great interest among researchers, since generation of optical frequency combs due to the quadratic nonlinearity may be realized at reduced pump powers because of the high level of the nonlinear response and in the spectral diapasons inaccessible for the conventional Kerr frequency combs. Also, it was shown that quadratic nonlinearity may support different types of the dissipative solitons (bright, dark and quasi-solitons) in optical microresonators upon second harmonic generation process [28,29] or via downconversion process (degenerate optical parametric oscillations) [30][31][32][33][34]. However, in a greater part of the previous studies the main attention was paid to the existence domains and properties of the localized states but not to their generation.…”
Section: Introductionmentioning
confidence: 99%
“…This fact aroused great interest among researchers, since generation of optical frequency combs due to the quadratic nonlinearity may be realized at reduced pump powers because of the high level of the nonlinear response and in the spectral diapasons inaccessible for the conventional Kerr frequency combs. Also, it was shown that quadratic nonlinearity may support different types of the dissipative solitons (bright, dark and quasi-solitons) in optical microresonators upon second harmonic generation process [28,29] or via downconversion process (degenerate optical parametric oscillations) [30][31][32][33][34]. However, in a greater part of the previous studies the main attention was paid to the existence domains and properties of the localized states but not to their generation.…”
Section: Introductionmentioning
confidence: 99%